Spatial Analysis of Tunisian Governorate-Level Health Efficiency - MRAD, FATMA; BOUABID, ANIS; JADAAN, HAITHAM S. (The journal of contemporary issues in business and government, 2021)
We investigate the differences of efficiency in health system between Tunisian governorates over the period 2010-2015 and examine how socioeconomic factors influence the regional distribution of the efficiency scores. The parametric stochastic frontier approach with fixed effects is employed to cacultate Tunisian governorate-level health efficiency scores. Spatial analysis tools are used to determine the spatial pattern of the efficiency scores and spatial econometric model are used to examine the impact of the socioeconomic and demographic factors on health efficiency. Our results show that education affects positively the efficiency of health system not only in region itself but also its neighbouring regions.However, the effects of unemployement are negative.